Telaah Ulang Teori ‘Urf; Mengurai Perdebatan Ulama’ Tentang Penggunaan ‘Urf Dalam Madzhab - Moh. Dliya'ul Chaq (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2018)
‘Urf in ushul fiqh is categorized as a source of Islamic law or a valid (disputed) Islamic legal proposition, but in the various products of Islamic jurisprudence that exist, it turns out that all schools use ‘urf as a source of law. The categorization seems to contradict the facts of the existing fiqh. Based on this, the focus of the study of this article is to unravel the ulama’ debate about the status of ‘urf in legal terms in each school. By using the library data analyzed in content (content analysis) in depth, it can be concluded that all schools use ‘Urf as a legal proposition or legal source even though the ushul fiqh is classified as a valid (disputed) legal proposition.